The anti-capitalist mentality and ill-fated transition: case of Serbia - Novaković, Aleksandar; Dostanić, Dušan (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2018)
This paper aims to show how the legacy of socialism with a human face represents a far more serious obstacle for the postsocialist transition than the heritage of rigid socialism. This is because an amalgamation of the perception of the autochthonous character of socialism accompanied by the perception of its soft, human face, creates an anti-capitalist mentality (Ludwig von Mises) that leaves an enormous impact on the long-term understandings of the concepts of individual, society, state, and reforms. This sort of mentality is deeply entrenched in Serbia, where a full-scale process of “debolshevization” has never been initiated. The continuity with socialist legacy is apparent in key segments of the ill-fated transition: political, institutional, economic, symbolical, and no less moral.